Review of Water Cooling Techniques for Enhancement Performance of Photovoltaic Panel - Faez Abid Muslim Abd Ali, Ahmed A. Taher, Muna Hameed Alturaihi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This study discusses various water-based cooling solutions for lowering the operative temperature of the electrical phenomena panel The goal of this review study is to improve the performance of micro electrical phenomenon the panel temperature the impact operative and temperature panel of electrical phenomena is explored using a variety of cooling strategies The advantages and disadvantages of evaporative cooling, water spray cooling, and immersion cooling were investigated in this research in order to determine their impact electrical phenomenon was well known evaporating cool system, which uses cold water to cool it, has effect with electrical phenomenon performance As a result, in a very hot climate, cool water was the ideal so improve electrical potency of electrical phenomenon